Multicentric investigation on the safety, feasibility and usability of the ABLE lower-limb robotic exoskeleton for individuals with spinal cord injury: a framework towards the standardisation of clinical evaluations - Wright, Mark Andrew; Herzog, Franziska; Mas-Vinyals, Anna; Carnicero-Carmona, Alfons; Lobo-Prat, Joan; Hensel, Cornelia; Franz, Steffen; Weidner, Norbert; Vidal, Joan; Opisso, Eloy; Rupp, Rüdiger (Journal of neuroEngineering and rehabilitation, 2023)
Robotic lower-limb exoskeletons have the potential to provide additional clinical benefits for persons with spinal cord injury (SCI). However, high variability between protocols does not allow the comparison of study results on safety and feasibility between different exoskeletons. We therefore incorporated key aspects from previous studies into our study protocol and accordingly conducted a multicentre study investigating the safety, feasibility and usability of the ABLE Exoskeleton in clinical settings.
Gesehen am 16.10.2023